2017
DOI: 10.1002/mrd.22930
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of proteomes between diabetic and normal human sperm: Insights into the effects of diabetes on male reproduction based on the regulation of mitochondria‐related proteins

Abstract: This study sought to identify sources of the reduced fertility of men with type 2 diabetes mellitus. Significant reductions in semen volume, sperm concentration, and total sperm count were observed in diabetic individuals, while transmission electron microscopy revealed that the structure of mitochondria in the tail of sperm from diabetic patients was damaged. Proteins potentially associated with these sperm defects were identified using proteomics. Isobaric tagging for relative and absolute quantitation label… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 25 publications
4
31
0
Order By: Relevance
“…Previous studies also supported our findings [61,62]. An et al [10] reported that no expression of the spermatogenesis regulator protein was recorded in the sperm of diabetic patients compared to normal. Decreased expression of other proteins in the sperm of diabetic patients was also reported by Kim and Moley [50] and Kriegel et al [61].…”
Section: Sperm Protein Concentration Protein Expression Via Sds-pagesupporting
confidence: 91%
“…Previous studies also supported our findings [61,62]. An et al [10] reported that no expression of the spermatogenesis regulator protein was recorded in the sperm of diabetic patients compared to normal. Decreased expression of other proteins in the sperm of diabetic patients was also reported by Kim and Moley [50] and Kriegel et al [61].…”
Section: Sperm Protein Concentration Protein Expression Via Sds-pagesupporting
confidence: 91%
“…Also the clinical pregnancy rate and the miscarriage rate was higher when the male partner was diabetic [65]. Another study of similar design also confirmed the presence of lower sperm concentration and total count in semen of diabetic patients compared with healthy individuals [66]. A study conducted in normozoospermic T2DM and non-diabetic men detected higher levels of malondialdehyde, a marker of oxidative stress, in diabetic patients that was consistent with lower sperm concentration, motility and normal morphology in this group compared with non-diabetic men [67].…”
Section: Glucose Metabolism and Male Fertilitymentioning
confidence: 87%
“…Such relatively higher abundance could explain why FT-spermatozoa from the EE were less functional than those retrieved from the SRF. For instance, one of these proteins, the dipeptidyl peptidase IV (DPP-IV or CD26), a mitochondrial-associated protein 26 related to sperm motility 27 , could be involved in inducing premature acrosome reaction when present in excess on the sperm surface. This protein is transferred to the sperm surface from sperm-binding seminal plasma vesicles 28 , and studies clearly demonstrated that human and bovine spermatozoa reach acrosome reaction if cultured with seminal plasma vesicles rich in DPP-IV 29,30 .…”
Section: Discussionmentioning
confidence: 99%